Mascot Design as a Branding Strategy for Serayu River, Kaliori Village, Banyumas Regency - Luqman Wahyudi; Ratih Alifah Putri; Famila Dwi Winati; Gilang Ramadhan (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Kaliori Village, located in Banyumas Regency, Central Java, is renowned for its rich arts and culture. Despite its cultural prominence, certain local potentials, such as the Serayu River, remain underdeveloped as tourism assets. This study aims to design a mascot as a branding strategy to enhance the Serayu River's image and promote it as a tourist destination. The method used included consultation, field observation, and collaborative design processes involving local communities and stakeholders. Results show that the